Exploring Soccer Fans’ Schemata Regarding Global VS Local Human Brands - Zarkada, Anna K.; Tzoumaka, Eugenia (My University, 2014)
Via an exploratory survey we decoded the interplay of the multiple points of attachment leading the consumer to the soccer field. Results indicate that local soccer player brands’ conceptual property which lies with the shared bond of team identification and is leveraged reciprocally, adds both to the human and the organizational brand equity.
Keywords: Soccer fans; Local human brands; Brand equity; Greek soccer club; Personal brand